2021
DOI: 10.1002/ase.2108
|View full text |Cite
|
Sign up to set email alerts
|

NOMENs land: The place of eponyms in the anatomy classroom

Abstract: The law of Non-Original Malappropriate Eponymous Nomenclature (NOMEN) states that no phenomenon is named after its discov-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…This eases communication and can provide evidence as to why clinicians would still use such terms. It is clearly fitting within Ferm and Lyons' definition quoted in the article, in that it does "develop medical vocabulary for use in diagnosis and communication as a physician" (Ferm & Lyons, 1971;McNulty et al, 2021).…”
Section: E T T E R T O T H E E D I T O R Eponyms Have a Place In The ...mentioning
confidence: 91%
See 3 more Smart Citations
“…This eases communication and can provide evidence as to why clinicians would still use such terms. It is clearly fitting within Ferm and Lyons' definition quoted in the article, in that it does "develop medical vocabulary for use in diagnosis and communication as a physician" (Ferm & Lyons, 1971;McNulty et al, 2021).…”
Section: E T T E R T O T H E E D I T O R Eponyms Have a Place In The ...mentioning
confidence: 91%
“…Having a period of phasing out the eponymous terms, as McNulty et al (2021) suggested, would surely then also create more confusion and invite a greater "risk of future legal action" Thus, eponymous terms are indeed indispensable.…”
Section: E T T E R T O T H E E D I T O R Eponyms Have a Place In The ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent viewpoint commentary, McNulty et al (2021) make the compelling case for removing eponymous terms from the anatomy classroom. Their argument is twofold: (1) the terms themselves are not descriptive of the anatomy and therefore increase the cognitive load of learners in a subject that already results in high cognitive loads; and (2) eponyms are often attributed erroneously, and the non-inclusive history of anatomy as a discipline means that eponyms are disproportionately attributed to white men, even when it is known that they were not the first to document or discover an anatomical structure.…”
Section: E T T E R T O T H E E D I T O R a Case For Using Eponyms In ...mentioning
confidence: 99%